Classics of Public Administration - Shafritz, Jay M. (Wadsworth/Thomson Learning, 2004)
CLASSICS OF PUBLIC ADMINISTRATION is a collection of articles carefully chosen for their readability and continuing contribution to the study of Public Administration. Written by the most significant scholars from the field, these classics focus on topics and issues that are recognized as important ongoing themes in the field of Public Administration